1982
DOI: 10.1136/bmj.284.6326.1365
|View full text |Cite
|
Sign up to set email alerts
|

Benoxaprofen: side-effect profile in 300 patients.

Abstract: Out of 300 patients who had taken benoxaprofen for a mean of 6 4 months, 196 These findings show that benoxaprofen is a potent phototoxic drug and that the manufacturers' recommended dosage of 600 mg daily is associated with an unacceptable incidence of side effects in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
1

Year Published

1983
1983
1995
1995

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(28 citation statements)
references
References 10 publications
0
27
0
1
Order By: Relevance
“…Approximately 10% of the administered dose is excreted unchanged in the urine (Ishizaki et al, 1979). It has been a clinical impression that adverse reactions to NSAIAs may be commoner in patients over the age of 65 years and a predisposition to adverse reaction in the aged was recently demonstrated in the case of benoxaprofen by Halsey & Cardoe (1982). Increased sensitivity to drugs in the elderly patient may result from a complex series of factors affecting both pharmacodynamics and pharmacokinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 10% of the administered dose is excreted unchanged in the urine (Ishizaki et al, 1979). It has been a clinical impression that adverse reactions to NSAIAs may be commoner in patients over the age of 65 years and a predisposition to adverse reaction in the aged was recently demonstrated in the case of benoxaprofen by Halsey & Cardoe (1982). Increased sensitivity to drugs in the elderly patient may result from a complex series of factors affecting both pharmacodynamics and pharmacokinetics.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical features associated with NSAID photosensitivity suggest a phototoxic, rather than photoallergic reaction (Halsey & Cardoe, 1982;Harber et al, 1982). Theoretically, phototoxic reactions should occur in 100% of the population if sufficient doses of drug and appropriate wavelengths of light are present.…”
Section: Introductionmentioning
confidence: 99%
“…Photosensitivity can be a clinically significant sideeffect in the treatment of RA patients using certain agents, such as NSAIDs [6] and has proved a particular problem with benoxaprofen [5,9]. Although the initial clinical study of benoxaprofen reported a 9% incidence of phototoxicity, other studies indicated that this adverse effect could significantly restrict the lifestyle of many patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although the initial clinical study of benoxaprofen reported a 9% incidence of phototoxicity, other studies indicated that this adverse effect could significantly restrict the lifestyle of many patients. Ferguson et al [8] found that most Caucasian subjects would respond abnormally providing that enough drug and irradiation were present, and Halsey & Cardoe [9] reported that about 50% of a series of 300 benoxaprofen-treated patients experienced photosensitivity during the summer months.…”
Section: Discussionmentioning
confidence: 99%